Transportation of liquid crystal and CaCO3 vaterite crystal in chicken embryo and early postnatal development. (13th April 2017) - Ling, Guo; Wang, Liyang; Rui, Feng; Li, Zhongguang; Wang, Juan; Ren, Kexing; Zhou, Xin; Ghartey-Kwansah, George; Xu, MengMeng; Jones, Odell; Yan, Guifang; Pan, Yuexin; et al.
ABSTRACT: During chick embryo development, the liquid crystals appear in more than 20 organs at certain developmental stages, and vanish in early post-natal stage. In this study, we found a complex in embryo, the YS-J/I tunnel system, in charge of transporting the LCs and CCVCs preserved from yolk sac into the embryo. This transportation initiates from yolk sac connecting to central transportation region/reservoir via a main tunnel, spreads radically to various parts of digestive system via sub-tunnels. Our data indicate that the liquid crystals could be the best form of nutrition which is necessary in embryo development and early post-natal development.